SHA-Based Health Accounts in 13 OECD Countries - Country Studies - Korea National Health Accounts 2001 - Jeong, Hyoung-Sun (OECD Health Technical Papers, 2004)
A project aimed at presenting initial results from the implementation of the System of Health Accounts has been carried by the Health Policy Unit at the OECD and experts from thirteen member countries. The results are presented in the form of a comparative study (OECD Health Working Papers No. 16) and a set of OECD Health Technical Papers presenting individual country studies. This volume is the seventh in this series, presenting the Korean SHA-based health accounts